EUS-guided gastroenterostomy using a novel electrocautery lumen apposing metal stent for treatment of gastric outlet obstruction (with video). Issue 5 (May 2023) - Mangiavillano, Benedetto; Larghi, Alberto; Vargas-Madrigal, Jorge; Facciorusso, Antonio; Di Matteo, Francesco; Crinò, Stefano Francesco; Pham, Khanh Do-Cong; Moon, Jong Hoo; Auriemma, Francesco; Camellini, Lorenzo; Paduano, Danilo; Stigliano, Serena; et al.
Abstract: Background and aim: Endoscopic ultrasound-guided gastroenterostomy (EUS-GE) for the treatment of gastric outlet obstruction (GOO) has been actually performed only with one type of electrocautery lumen-apposing metal stents (EC-LAMS). We aimed to evaluate the safety, technical and clinical effectiveness of EUS-GE using a newly available EC-LAMS in patients with malignant and benign GOO. Materials and methods: Consecutive patients who underwent EUS-GE for GOO using the new EC-LAMS at five endoscopic referral centers were retrospectively evaluated. Clinical efficacy was determined utilizing the Gastric Outlet Obstruction Scoring System (GOOSS). Results: Twenty-five patients (64% male, mean age 68.7 ± 9.3 years) met the inclusion criteria; 21 (84%) had malignant etiology. Technically, EUS-GE was successful in all patients, with a mean procedural time of 35 ± 5 min. Clinical success was 68% at 7 days and 100% at 30 days. The mean time to resume oral diet was 11.4 ± 5.8 h, with an improvement of at least one point of GOOSS score observed in all patients. The median hospital stay was 4 days. No procedure-related adverse events occurred. After a mean follow-up of 7.6 months (95% CI 4.6–9.2), no stent dysfunctions were observed. Conclusion: This study suggests EUS-GE can be performed safely and successfully using the new EC-LAMS. Future large multicenter prospective studies are needed to confirm our preliminary data.